Analysing the Role of Language in Personal Growth: A Systemic Functional Study on Akeelah’s Discourse - Nasution, Lisa Anna (Journal of English Language and Education, 2026)
This study analyzes the metafunctions of language (ideational, interpersonal, and textual) in Akeelah's discourse in the film Akeelah and the Bee (2006) and how they relate to her personal growth in an educational context. A gap was found, namely the lack of research that pays attention to the social and personal functions of language in the learning process. This is where the novelty of this study lies, the Systemic Functional Linguistics approach is applied in depth in the analysis of film media as a representation of language learning. Using a qualitative approach and Systemic Functional Linguistics (Halliday), 20 discourses were purposively selected for analysis. The findings show that the ideational metafunction reflects her thoughts and identity development. Akeelah's use of language serves as both a mirror and a driver of her transformation as a learner. This insight contributes to English language teaching by emphasizing the role of language in supporting motivation and identity.